Connectedness between oil and agricultural commodity prices during tranquil and volatile period. Is crude oil a victim indeed?. (August 2021) - Sun, Yanpeng; Mirza, Nawazish; Qadeer, Abdul; Hsueh, Hsin-Pei
Abstract: Increasing financialization of energy and commodity markets offer a variety of tradeoff for the investors and consumers. On the one hand, this increased financialization of the two markets helps investors design a well-diversified investment portfolio with assets from different asset categories. However, at the same time, this increases the connectedness between the two markets significantly, which may have strong implications for investors and consumers. In this paper, we examine the long-term connectedness and causality between Crude oil and agricultural commodity prices. The advantage of long-term time series is that we may be able to uncover the demand and supply shocks that originated in both markets during the tranquil period and the shocks during the volatile period such as the Global Financial Crisis of 2008 and COVID-19 pandemic. For this purpose, we employ the full bootstrap sample and rolling window causality tests primarily. Our results are surprisingly different from most of the studies that have held oil prices responsible for causing changes in agricultural commodity prices (ACP). In contrast, our results confirm the presence of bidirectional causality and show that Oil prices are as much affected by the ACP as vice versa. This significant reverse causality running from ACP to Oil prices can open up a completely new interpretation domain. Finally, it is surprisingly interesting that both ACP and Oil prices remain immune to the shocks that originated in both markets during the entire time period of the COVID-19 pandemic. Highlights: We examine the long-term connectedness and causality between crude oil prices and agricultural commodity prices (ACP). We employ the time series method to uncover shocks during the tranquil period and volatile period. Surprisingly, our results are different from existing studies that have held oil prices responsible for causing ACP changes. Our results confirm the presence of bidirectional causality between Oil prices and agricultural commodity prices.